ESTIMATION OF FERMA CURVES PARAMETERS FOR UNIVERSAL HASHING OF NUMBER SOLUTION FOR HURVITZ EQUATION IN THE FINITE FIELD - Khalimov, G. Z. (Radio Electronics, Computer Science, Control, 2011)
Exact solutions for a number of Ferma curves points when the field order has dividers 2, 3 and 6 as well as estimates of points number have been obtained using probabilistic approach. Asymptotic boundaries of the ratio of maximum number of Ferma curve points in a simple field to its genus and to Hasse–Weil boundary are given.